P165Magnesium orotate in high concentration elicits cardioprotection via modulation of mitochondrial functions. (15th July 2014) - Duicu, O M; Gorbe, A; Privistirescu, A; Mirica, N S; Csont, T; Ferdinandy, P; Muntean, D M
Abstract: Modulation of mitochondrial function in the settings of ischemia/reperfusion (I/R) injury represents a major therapeutic target of pharmacological agents able to reduce the cell death at reperfusion. The aim of this study was to compare the effects of acute administration of magnesium orotate (MO), MgCl2, orotic acid (OA) with those elicited by the classic mitochondrial permeability transition pore (mPTP) desensitizer, cyclosporine A (CsA) in two experimental settings. The pharmacological agents were administered: i) at reoxygenation in neonatal cardiomyocytes subjected to 4 hours simulated ischemia followed by 2 hours reoxygenation with the assessment of cell viability and reactive oxygen species (ROS) generation, and ii) at reperfusion in isolated rat hearts subjected to 30 min of global ischemia and 120 min of reperfusion. In the latter model myocardial functional recovery (at 30 min of reperfusion) and infarct size (at 120 min of reperfusion) were assessed. In a separate group of animals, mitochondria were isolated at 15 min of reperfusion after global ischemia, and mitochondrial respiration, ROS production (Amplex Red) and calcium retention capacity were assessed. Acute administration of 5 mM MO, MgCl2, OA or 1 μM CsA in neonatal cardiomyocytes subjected to simulated ischemia/reoxygenation enhanced cell survival; these protective effects were not associated with changes in ROS production during reoxygenation. During the postischemic reperfusion in rat hearts and isolated mitochondria, respectively, MO, MgCl2 (5 mM both) and CsA (0.2 μmol/L), but not OA: (i) induced an important recovery of left ventricular end-diastolic pressure (LVDP), and decreased infarct size vs. controls, and (ii) protected against loss of outer mitochondrial membrane integrity and subsequent deficits in electron transport and also inhibited the calcium triggered-mPTP opening. In particular, the effects of MO were comparable to the ones elicited by CsA. In conclusion, acute administration of magnesium orotate in high concentration during the postischemic reperfusion is associated with cardioprotective effects via modulation of mitochondria functions.